The Effect of Dividend Policy, Risk Management, and Institutional Ownership on Financial Performance with Capital Structure as a Moderating Variable (an Empirical Study on the Consumer Non-Cyclicals Sector Listed on the Indonesia Stock Exchange) - Cahyati, Novia Dwi; Suryadi, Edy (UNIVERSITAS PAKUAN, 2025)
This study aims to examine the influence of Dividend Policy, Risk Management, and Institutional Ownership on Financial Performance, with Capital Structure as a moderating variable. Using a quantitative approach and secondary data from non-cyclical consumer companies listed on the Indonesia Stock Exchange between 2022 and 2024, this study applies moderated regression analysis to test the proposed hypotheses. The model used meets all classical assumptions and is therefore considered appropriate for analysis. The results indicate a very weak relationship between the variables studied, with only 2.7% of financial performance variation explained by the independent variables and their interaction with Capital Structure. Both simultaneous and individual variable tests did not show a significant effect on financial performance. Additionally, Capital Structure does not significantly moderate the relationship between the independent variables and financial performance. These findings suggest that investors and stakeholders should consider additional factors beyond the variables studied to evaluate company performance more comprehensively. Further research is recommended to include broader variables such as operational efficiency, leverage, liquidity, and corporate governance, while using larger and more diverse datasets to improve generalizability and provide deeper insights.